Managerial Ability and Real Earnings Management Among Indian Listed Firms - Manish Kumar; Rishabh Goswami
This study aims to discover whether managers of Indian listed firms with extraordinary managerial abilities refrain from real earnings management (REM). The measure of managerial ability used in this study is based on the firm$1 (Bs ability to utilize its resources into sales revenue. To examine the relationship between managerial ability and REM, a fixed-effect model is used on a balanced panel of 108 National Stock Exchange-listed non-financial firms from 2006 to 2017. The findings of the study provide empirical evidence indicating that a proficient manager is more likely to refrain from REM. The decrease in REM with an increase in managerial ability is on account of containing REM in overproduction by managers with higher abilities. Besides, the study also finds a complementary association between REM and accruals-based earnings management.s